Frequency of Tuberculosis in Patients with Lung Cancer - Aneel Kumar, Raniyah Akhter, Neelam Khtari, Nausheen Saifullah, Nadeem Ahmed Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the tuberculosis frequency in lung cancer patients. Study Design: Descriptive, cross-sectional study. Place and Duration of Study: Department of Pulmonology, Jinnah Postgraduate Medical Center, Karachi from 11th September 2017 to 10th March 2018. Methodology: One hundred and seventeen patients with lung cancer of age 30-60 years and both genders were enrolled. Patients with already taking anti-tuberculous therapy, previous history of tuberculosis, chest trauma and surgery were excluded. The relevant history, sputum or bronchial lavage sample was taken and presence or absence of pulmonary tuberculosis was noted. Results: Mean age was 50.31±6.43 years and majority of the patients 99 (84.62%) were between 46 to 60 years of age. Seventy five (64.10%) were male and 42 (35.90%) were females. Mean duration of disease was 17.97±4.67 days. Tuberculosis in patients with lung cancer was found in 24 (20.51%) patients whereas 93 (79.49%) patients have no tuberculosis. Conclusion: The frequency of tuberculosis in patients with lung cancer is quite high. Keywords: Tuberculosis, Lung cancer, Morbidity